Back from the dead: extracorporeal rewarming of severe accidental hypothermia victims in accident and emergency. Issue 4 (July 1997) - Ireland, A J; Pathi, V L; Crawford, R; Colquhoun, I W
Abstract : Severe accidental hypothermia in an urban environment is usually associated with drug or alcohol abuse or serious illness in elderly or debilitated patients. In the presence of cardiovascular instability, extracorporeal rewarming by cardiopulmonary bypass is the gold standard of treatment of such patients. Three cases of profound hypothermia with circulatory collapse are presented. Each was successfully resuscitated to a full neurological recovery using this method in an accident and emergency (A&E) department, although one died later of respiratory complications. All three cases had a serum potassium in the normal range at the start of treatment. Where facilities exist, extracorporeal rewarming can be performed in A&E for patients with profound hypothermia and circulatory collapse. Cardiopulmonary resuscitation must be continued throughout the rewarming process.